IMPLEMENTASI FUNGSI MANAJERIAL KEPALA SMP - Idris, Muhammad (Pascasarjana Universitas Negeri Makassar, 2015)
managerial fuction on the aspects of the planning, organization, leaderships, monitoring, evaluation as well as the supporting and inhibiting factors of the principal in managing the school. The study was conducted at SMPN 4 Panca Rijang in Sidenreng Rappang district. The data sources were 9 informants which consisted of the principal, the vice principals, of curriculum affairs, students affairs, facility and infrastucture affairs, public relation affairs, administration affairs, subject teachers, and the chief of school committe. Data were collected through in-depth interview and documentation. Data were then analyzed by employing qualitative method with several steps: data reduction, data persentation, data verification, and member check. The result of the study revealed that the implementation of the principal’s managerial function on the palnning aspect was conducted well, indicated by the success of the principal in arranging the plan of the various level, RAPBS. The organization aspect was conducted well, indicated by the successof the principal in arranging the organizational structure of the school, job distribution, and job delegation. The leadership aspect was not conducted well due to less maximal of the human resoursces in school. The monitoring aspect was not conducted well as well due to less maximal of the principal in controlling the school activities, particulary the teaching and learning process in class. The evaluation aspect was conducted well, indicated by the implementation of evaluation on the activities which appropriated with the plan according to the procedure, time allocation, and the set funding. The supporting factors of the principal in managing the school were professional leadership, the education qualification of the teachers and employees who are sarjana in everage, harmonious partnership between the stakeholders; whereas, the inhibiting factors were inefficient facility and infrastructure, school condition in terms of flooding, lack of participation by the public, material and non-material factors of the parents.